ADOPSI TECHNOLOGY ACCEPTANCE MODEL (TAM) TERHADAP PERILAKU MINAT GENERASI MILENIAL DALAM BERINVESTASI DI PASAR MODAL - Purboyo; Lamsah; Aida Vitria (JWM (JURNAL WAWASAN MANAJEMEN), 2020)
This study aims to determine the effect of technology acceptance on the interests of the millennial generation to invest in the capital market. The adoption of the TAM model was used in this study, with a quantitative descriptive method approach, data collection using a questionnaire with a sample of 135 people based on calculations with the Slovin formula. Data were analyzed using smart partial least square. The results of this study provide answers to the proposed hypothesis in which the variable perceived ease of use, perceived usefulness, perceived enjoyment have a positive and significant effect on the variable of behavioral intention to use, then the variable perceived enjoyment and behavioral intention to use also have a positive and significant effect on variables actual to use, but there is one variable that does not significantly influence the effect of the variable perceived usefulness on the variable actual to use. This research clarifies how the role of technology applied in online stock trading can influence the behavior of the interests of investors in the Indonesian capital market, especially among millennials. This research is expected to be useful for the development of science and for the development of capital markets with a clearer understanding of how the TAM model influences the behavior of millennial generation interests to become investors in the capital market.